Etiología de las alteraciones en mucosa oral y periodontal en pacientes con SARS-COV-2. Revisión narrativa (2022)
The covid-19 disease generated a global emergency that ended with a declaration of a pandemic and a total lockdown of all people and establishments. In the case of Colombia, it began with a selective isolation given under Decree 206 of February 26, 2021, which regulated the phase of selective isolation and responsible individual distancing in the Republic of Colombia in the framework of the health emergency due to of the new Coronavirus. Subsequently, for the month of March, the total confinement of all people took place. It is then that many people were unable to attend general health services again, especially dentistry, since the risk of contagion was very high.